2020
DOI: 10.7759/cureus.7058
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Area Postrema Syndrome Presenting as Intractable Nausea and Vomiting

Abstract: Neuromyelitis optica (NMO) is a disease of central nervous system, characterized by demyelination and axonal damage mostly involving optic nerves and spinal cord. Usually these patients present with symptoms related to optic neuritis or myelitis with a typical relapsing course. Some patients present with less common symptoms involving brain stem like nausea and vomiting, especially those involving area postrema (AP) located in dorsal medulla. International panel for NMO diagnosis revised criteria in 2015 and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…On the other hand, although APS is considered highly specific for AQP4-seropositivity [14,19,32,[46][47][48] APS in AQP4-seronegative patients (including patients with anti-Myeline oligodendrocyte glycoprotein "MOG"-IgGs) are being increasingly recognized [39]. Three AQP4-seronegative cases were identified in the present study (15%) and tested positive for anti-MOG.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…On the other hand, although APS is considered highly specific for AQP4-seropositivity [14,19,32,[46][47][48] APS in AQP4-seronegative patients (including patients with anti-Myeline oligodendrocyte glycoprotein "MOG"-IgGs) are being increasingly recognized [39]. Three AQP4-seronegative cases were identified in the present study (15%) and tested positive for anti-MOG.…”
Section: Discussionmentioning
confidence: 64%
“…Most studies of NMOSD have focused on the classic opticospinal presentations, while only few outlined other presentations including APS and were mainly case reports [11][12][13][14][15][16][17][18][19][20][21]. By conducting this study, we aimed to investigate the frequency and diagnostic challenges in NMOSD patients with APS from the south of Egypt with a description of their clinical and radiological features.…”
Section: Introductionmentioning
confidence: 99%
“…In a neuropathologic study, Popescu et al demonstrated that the area postrema was a selective target of disease processes in patients with NMOSD and suggested that patients with lesions in this area were more likely to present with nausea and vomiting [ 7 ]. Some case studies reported patients with unexplained nausea and vomiting who were later diagnosed with NMOSD [ 8 12 ]. The reported frequency of isolated APS at the time of NMOSD onset is 7.1% to 14% [ 1 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neuromyelitis optica spectrum disorder is a rare, serious autoimmune condition with significant morbidity and mortality. The disorder is characterized by demyelination and axonal damage that typically involve the optic nerve or spinal cord ( 1 , 2 ). NMOSD is typically associated with autoantibodies that target aquaporin-4, an abundant water channel in the central nervous system ( 1 ).…”
Section: Discussionmentioning
confidence: 99%